PENINGKATAN KINERJA GURU DALAM PEMBELAJARAN DI KELAS MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK DI SMA NEGERI 7 DENPASAR - Cokorda Gede Anom Wiratmaja (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
Educational supervision is supervision directed at the learning curriculum, teaching and learning process, implementation of guidance and counseling. The aim is to describe the steps for periodic collaborative educational supervision of teachers in preparing lesson plans, implementing learning, assessing learning achievement, and carrying out follow-up assessments of student learning achievement at SMA Negeri 7 Denpasar in the 2021/2022 academic year. The subjects in this study were teachers of SMA Negeri 7 Denpasar, which consisted of 12 teachers who were randomly selected for each field of study. This type of research is school action research. The action research was carried out in two cycles and in each cycle there were four activities, namely planning, action, observation, and reflection. Data collection techniques in this study consisted of four main activities, namely initial data collection, data analysis results at the end of each cycle, and other responses from teachers to the implementation of collaborative educational supervision. The results of the study indicate that the implementation of periodic collaborative educational supervision can improve teacher performance in preparing lesson plans. The implementation of periodic collaborative educational supervision can improve teacher performance in assessing student achievement. The implementation of periodic collaborative educational supervision can improve teacher performance in carrying out follow-up on the results of student achievement assessments.